Totall synthesis of (+/-)-sacidumllignan D - Pandey, Sunil Kumar; Ramana, C. V. (Journal of Organic Chemistry, 2011)
The first total synthesis of (+/-)-sacidumlignan D featuring a Zn-mediated Barbier reaction and reverse Wacker oxidation to form the key gamma-lactone, its diastereoselective alpha-methylation followed by reduction cyclization, was documented.